Wpływ wspólnej waluty europejskiej na rozwój sektora rolno-spożywczego - Zawojska, Aldona (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
The introduction of the euro as a part of the Economic and Monetary Union on 1 January 1999 could have important implications for the whole economy of the Member States and for its selected sectors, namely for agro-food industry. It will affect common agricultural policy as well. This paper examines macro-economic effects of the single currency in the European Union and for Associated States. It outlines the main economic costs and benefits of the euro for farmers and agro-food enterprises in the European Union. Furthermore, it discusses changes in the agri-monetary system and analyses the impacts of the euro on farm prices, direct payments and agricultural income as well as on rural development. The effects of the euro on the EU agricultural budget were also presented. The advent of the euro means the end of the agri-monetary system in the form it took up to the end of 1998. It will lead to changes in producer prices and payments. In the short term, the impact on farm incomes will depend on the arrangements each country makes when institutional prices and direct payments are set in euros. In the longer term, the euro/dollar exchange rate is likely to be the most important factor for prices and incomes.